The Effect Of Youtube Content Development Traditional Games In The Motor Development Of Early Children In The New Normal Era - Ghossania, Nabila Ayu; Tasu'ah, Neneng (Jurusan PGPAUD FIP UNNES, 2023)
Motor development is a continuous proces sof development and occurs significantly for bone formation, growth and development, movement of muscles and nerves according to their age range which will affect children's skills in moving. This motoric development canbe developed through play activities. The purpose of this research is to find out the development of You Tube content for traditional games in the motor development of early childhood in the new normal era at TPQ Baiturrahman Jatisari. The method used is an experimental research method. The experimental design uses aquasi-experimental design.The instruments used include observation sheets, pre-test and post-test. Data analysis by grouping data based on variables and types of respondents, tabulating data based on variables from all respondents,then presenting data one achvariable studied, performing calculations to answer the problem formulation,then performing calculations to test the hypotheses that have been proposed.The results showed an average score of 81.60% before and after the traditional game treatment. So, it can be said that the activity of children while playing affects the motor skills of early childhood. The development of You Tube content through traditional games has an effect on the motor skills of children aged 5-6 years. This means that traditional games can be applied in schools witha level of effectiveness through consideration as an effort to improve early childhood motor skills. The N-Gain test has reached the expected indicator of 81.60%. This shows that the use of YouTube content development methods through traditional games can improve motor development in early childhood. Besides that, it can be used as an alternative teacher in an effort to introduce traditional games to early childhood.